DATA TERKINI BAHASA MINANGKABAU MELALUI PENAMAAN DAERAH: (Upayakan Pembudayaan Bagi Keaslian Nama Daerah Di Sumbar) - Welya Roza; Zulkarnaini Zulkarnaini; Muslim Tawakal (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2020)
This article covers the effort to restore the originality of regional names in West Sumatra. The effort aims to fulfill the mandate of UUD 1945.The chapters and verses on the language are included in Section XV, Article 36 UUD 1945 Subsection (4) mentions: